Griseofulvin and Fluconazole Reduce Transmission of Tinea Capitis in Schoolchildren. Issue 5 (27th July 2015) - Shemer, Avner; Grunwald, Marcello H.; Gupta, Aditya K.; Lyakhovitsky, Anna; Daniel, Carlton Ralph; Amichai, Boaz
Abstract Objective We evaluated the efficacy of griseofulvin and fluconazole in reducing the potential for person‐to‐person transmission of tinea capitis (TC) in children. Methods Children with TC with positive fungal cultures were treated with griseofulvin 25 mg/kg/day (group A) or fluconazole 6 mg/kg/day (group B) for at least 21 days and up to 12 weeks until cure was achieved. Clinical and mycologic examinations occurred before treatment and on days 3, 7, 10, 14, and 21 of treatment. During each visit, mycologic examination was performed from scalp lesions of children and fingertips of medical staff and parents after a brief touch of the patient's scalp lesions. Results Ninety patients were enrolled: 48 treated with griseofulvin and 42 with fluconazole. The predominant species were Trichophyton violaceum (n = 44) and Microsporum canis (n = 41), followed by Trichophyton mentagrophytes (n = 3) and Trichophyton rubrum (n = 2). Ten days after treatment more than 75% of patients from both treatment groups were noncontagious. At day 21, all patients from group A were noncontagious and two (7%) with positive culture of M. canis from group B were still contagious. Conclusions No statistically significant differences were found between treatment groups. Griseofulvin and fluconazole reduced the potential for disease transmission in children with TC, with griseofulvin being more effective for M. canis infections, although children with TC may be potentially contagious even after up to 3 weeks of treatment. These data should be considered regarding school attendance of children with TC.